Predição do ruído aerodinâmico da pá de um típico aerogerador de grande porte - Sousa, Felipe Martins de (2017)
Studies and research indicate that the Northeast of Brazil is the region of this country more propitious for the generation of wind energy, especially in the states of Ceará and Rio Grande do Norte. In addition to the wind potential, the emitted noise is an important factor in determining the location of wind turbine installation, which makes it difficult to accept its installation due to the annoyance and health problems caused by the noise emission. In this way the noise estimation is one of the most relevant aspects in the installation of a wind turbine. The present work has as main objective the prediction of the aerodynamic noise of the blade of a typical large aerogenerator, based on the acoustic analogy of Ffowcs-Williams and Hawkings (FW-H) with the help of CFD (Computational Fluid Dynamics) commercial ANSYS Fluent. Simulations were performed with the LES turbulence model in two dimensions in different sections along the blade and in three dimensions in the complete blade without rotation. The results obtained in the simulations by the FW-H acoustic analogy show that the noise is higher in the sections closer to the blade tip, because the wind flow is increasing as it approaches this region. The data obtained in the three-dimensional simulations indicate that the noise upstream and downstream of the rotor plane have the highest values compared to those obtained in the rotor plane.